Energy Regulation and Energy Trade: International Evidence - Tran, Ha Manh; Bui, Trung Huy (International Journal of Energy Economics and Policy, 2025)
This study investigates the impact of energy regulation on energy trade by employing an extended gravity model with bilateral trade data from the CEPII BACI database and regulatory information from the World Bank’s Regulatory Indicators for Sustainable Energy, covering 126 countries from 1996 to 2021. The findings reveal that stronger energy regulations significantly promote energy trade, with both exporter-side and importer-side regulations playing important roles. Disaggregated analysis shows that solar and wind, biomass, and geothermal energy trades are positively influenced by regulatory improvements, while hydro and marine energy show limited responsiveness. Further examination across income groups highlights that emerging markets benefit most from stronger regulations, advanced economies face trade reductions due to stricter regulatory frameworks, and low-income economies experience no significant regulatory effect. These findings underscore the importance of tailored regulatory policies that consider economic contexts and sector-specific characteristics. The study offers valuable insights for policymakers aiming to promote sustainable energy trade through effective regulation.